Design, modification of phyllanthone derivatives as anti-diabetic and cytotoxic agents. Issue 1 (22nd December 2021) - Nguyen, Ngoc-Hong; Vo, Van-Giau; Phan, Hoang-Vinh-Truong; Ngo, Thanh-The; Sichaem, Jirapast; Nguyen, Thi-Phuong; Nguyen, Huu-Hung; Pham, Duc-Dung; Nguyen, Tien-Cong; Nguyen, Van-Kieu; Duong, Thuc-Huy
Abstract: Twelve benzylidene derivatives, one Baeyer-Villiger oxidative, six imine derivatives were successfully designed and synthesised from phyllanthone. In the search for potential new anti-diabetic agents, phyllanthone along with its benzylidene and oxidation analogues were evaluated for enzyme inhibition against α -glucosidase. In the benzylidene series, most analogues displayed stronger activity than the mother compound. Compound 1c revealed the strongest activity, outperforming the acarbose positive control with an IC50 value of 19.59 µM. Phyllanthone and its derivatives were then tested for cytotoxic activity against the K562 cell line. The imine analogues displayed the most powerful cytotoxic activity with 3c and 3d having IC50 values of 57.55 and 68.02 µM, respectively. Graphical Abstract: UF0001